Sovietization in Romania and Czechoslovakia : history, analogies, consequences - edited by Alexandru Zub & Flavius Solomon in cooperation with Oldřich Tůma & Jiří Jindra. (Polirom, 2003)
Donation from Catalina Mihalache.